2023
DOI: 10.3390/life13041032
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hormone Types, Concentrations, and Treatment Times on the Rooting Traits of Morus ‘Yueshenda 10’ Softwood Cuttings

Abstract: Enhancing the capacity of fruit trees to propagate via cuttings is an important endeavor for the high-quality development of the fruit industry. Optimizing the conditions for the cutting propagation of mulberry seedlings is an important factor that influences the industrial production of this plant; however, the currently used mulberry breeding technology system is not mature. In this experiment, an orthogonal design was used to intercept semi-woody shoots of Yueshenda 10 as cuttings and set different hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
0
0
3
Order By: Relevance
“…Durango and Humanez (2017) indicate that as auxin concentrations increase, the number of roots decreases. Similarly, Sun et al (2023) observed the same pattern as the NAA and IBA concentration gradually increased within the range of 0~200~500~800 mg L -1 ; the rooting rate, average number of roots, maximum root length and rooting efficiency index initially increased followed by a decrease when applying a concentration of 1,000 mg L -1 . Salinas et al (2022) indicate that the spatial pattern of auxin accumulation at the tissue level may be due to a combination of localized auxin biosynthesis and nonpolar (in areas of high auxin concentration) and polar transport through cells.…”
Section: Rooting and Sproutingsupporting
confidence: 62%
“…Durango and Humanez (2017) indicate that as auxin concentrations increase, the number of roots decreases. Similarly, Sun et al (2023) observed the same pattern as the NAA and IBA concentration gradually increased within the range of 0~200~500~800 mg L -1 ; the rooting rate, average number of roots, maximum root length and rooting efficiency index initially increased followed by a decrease when applying a concentration of 1,000 mg L -1 . Salinas et al (2022) indicate that the spatial pattern of auxin accumulation at the tissue level may be due to a combination of localized auxin biosynthesis and nonpolar (in areas of high auxin concentration) and polar transport through cells.…”
Section: Rooting and Sproutingsupporting
confidence: 62%
“…Menurut Upe (2019), tanaman memerlukan ZPT dalam konsentrasi yang sesuai untuk pertumbuhannya. Ditambahkan oleh Sun et al (2023) bahwa ZPT efektif dalam konsentrasi tertentu, konsentrasi yang terlalu rendah atau terlalu tinggi membuat ZPT bekerja tidak efektif.…”
Section: Persentase Stek Hidup Stek Berakar Stek Bertunas Dan Stek Be...unclassified
“…Peran penting natrium nitrofenol yang merupakan ZPT anorganik dan ekstrak bawang merah yang merupakan ZPT organik yang keduanya mengandung auksin berperan penting dalam meningkatkan pertumbuhan tanaman. Hasil penelitian Sun et al (2023) menunjukkan bahwa bahan auksin mudah terserap ke dalam jaringan tanaman sehingga mempercepat aliran protoplasma menunjang pertumbuhan akar stek. Gomes et al (2020) menambahkan bahwa proses pembentukan akar merupakan faktor terpenting yang mendorong pertumbuhan dan pelestarian stek, karena akar tersebut menyerap unsur hara dari dalam tanah.…”
Section: Persentase Stek Hidup Stek Berakar Stek Bertunas Dan Stek Be...unclassified
See 1 more Smart Citation
“…After auxin treatment the apical shoot cuttings were planted in polybags containing different rooting medium. The 1/3 basal cut portion was inserted in different rooting media using sticking technique [17]. In order to make complete wetting on entire cut surface, holes were made in each bag to avoid the damage of cambium and to prevent the removal of rooting hormone.…”
Section: Optimize the Rooting Medium For Mini Clonal Propagationmentioning
confidence: 99%